Multifunctional micro / nano fiber material for efficient air filtration as well as preparation method and application of multifunctional micro / nano fiber material

The multifunctional micro/nanofiber materials prepared by self-assembly method combined with metal-organic supramolecular nanofiber network solve the shortcomings of existing air filter materials in filtration performance, production scalability, humidity stability and antibacterial functions, and achieve high-efficiency particle capture, low air resistance, excellent breathability and antibacterial properties.

CN120459717AActive Publication Date: 2025-08-12TIANJIN POLYTECHNIC UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510608702.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-08-12
Estimated Expiration
2045-05-13

AI Technical Summary

Technical Problem

Existing air filter materials have shortcomings in filtration performance, production scalability, humidity stability and antibacterial functions, making it difficult to balance high-efficiency particle capture, low air resistance, excellent breathability and biodegradability.

Method used

A multifunctional micro/nanofiber material of micro-scale fiber scaffold layer and nanofiber layer was prepared by self-assembly method, and polylactic acid scaffold was prepared through meltblown process and dip coating was performed to form an ultrafine metal-organic supramole network.

Benefits of technology

It has achieved efficient particle capture capability, low air resistance, humidity stability and antibacterial properties, significantly improved filtration efficiency, breathability and moisture management capabilities, and enhanced health protection and material scalability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120459717A_ABST
    Figure CN120459717A_ABST
Patent Text Reader

Abstract

The invention provides a multifunctional micro / nano fiber material for efficient air filtration and a preparation method and application thereof, the multifunctional micro / nano fiber material comprises a micron-sized fiber support layer and a nano fiber layer growing on the micron-sized fiber support layer, the nanofiber layer is synthesized by a metal ion donor and an organic ligand L through a self-assembly method. The filtering material disclosed by the invention has excellent antibacterial property, air permeability and moisture management capability while realizing high filtering efficiency and low air resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of air filtration, and in particular relates to a multifunctional micro / nano fiber material for high-efficiency air filtration, a preparation method thereof, and an application thereof. Background Art

[0002] Air filters are widely used in environmental purification and public health protection. Meltblown nonwovens, due to their three-dimensional mesh structure and electrostatic electret effect, dominate air filtration applications (Polymers 2020, 12 (10), 2341). However, electret meltblown nonwovens will experience a decrease in filtration efficiency due to electrostatic decay under high humidity conditions, limiting their long-term stability. In addition, there is a trade-off between filtration efficiency and air resistance for micron-sized meltblown fibers (Small 2017, 13 (46), 1702139), making it difficult to maintain excellent air permeability while ensuring efficient particle capture. To overcome the limitations of meltblown materials, nanofiber membranes have been used as high-efficiency air filtration materials due to their high specific surface area and fiber fineness (Ind. Eng. Chem. Res. 2021, 60 (20), 7517–7534.). Electrospun nanofiber membranes excel in capturing submicron particles, but due to the small gaps between nanofibers, limited air permeability, and low yields of conventional electrospinning methods, large-scale production is difficult (Applied Materials Today 2019, 17, 1–35). In recent years, multi-scale fiber structures have been proposed to optimize filtration efficiency, air resistance, and moisture management (Sci. China Mater. 2019, 62(3), 423–436). This strategy combines the high air permeability of micron-sized support fibers with the efficient particle retention capacity of the nanofiber layer, improving overall filtration performance. However, existing methods for preparing layered structures, such as electrospinning combined with meltblowing, still face problems such as low production efficiency and poor adhesion of the nanofiber layer, and there are still challenges in achieving antibacterial and biodegradable properties.

[0003] Therefore, the existing technology still has shortcomings in filtration performance, production scalability, humidity stability and antibacterial function. There is an urgent need for an air filtration material with high filtration efficiency, low air resistance, excellent antibacterial properties and biodegradability to meet the increasingly stringent needs of environmental purification and health protection. Summary of the Invention

[0004] In view of this, the present invention aims to overcome the defects in the prior art and proposes a multifunctional micro / nano fiber material for high-efficiency air filtration and a preparation method and application thereof.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] In a first aspect, the present invention provides a multifunctional micro / nanofiber material for high-efficiency air filtration, wherein the multifunctional micro / nanofiber material comprises a micron-sized fiber support layer and a nanofiber layer grown on the micron-sized fiber support layer, wherein the nanofiber layer is synthesized from a metal ion donor and an organic ligand L by a self-assembly method.

[0007] Preferably, the organic ligand L is tris(3-pyridyl)benzene-1,3,5-tricarboxylate, and its structural formula is:

[0008]

[0009] Preferably, the silver metal salt is selected from one or more of AgNO3, AgBF4, AgClO4, and AgCF3SO3, the trivalent iron metal salt is FeNO3, the copper metal salt is CuSO4, the zinc metal salt is ZnCl2, the cobalt metal salt is CoCl2, and the nickel metal salt is Ni(NO3)2·6H2O or NiCl2·6H2O. Further preferably, the metal salt is a silver metal salt or a trivalent iron metal salt.

[0010] Preferably, the molar ratio of the organic ligand L to the metal salt is 2:3.

[0011] Preferably, the micron-scale fiber scaffold layer is made of polylactic acid with a weight-average relative molecular mass Mw of 100,000-300,000 and is prepared by a melt-blowing process.

[0012] In a second aspect, the present invention provides a method for preparing a multifunctional micro / nano fiber material for high-efficiency air filtration, comprising the following steps:

[0013] S1: melt-blown process to prepare the polylactic acid scaffold layer;

[0014] S2: dissolving an organic ligand L in an organic solvent I to form a solution A, and dissolving a metal salt in an organic solvent II to form a solution B, wherein the molar ratio of the organic ligand L to the metal salt is 2:3;

[0015] S3: The polylactic acid scaffold layer prepared in step S1 is sequentially immersed in solution A and solution B for dip coating. The polylactic acid scaffold layer after dip coating is air-dried and dried at room temperature to obtain a multifunctional micro / nano fiber material.

[0016] Preferably, the mass fraction of the ligand L in the solution A is 0.08%-0.15%.

[0017] Preferably, the mass fraction of the metal salt in the solution B is 0.05%-0.09%.

[0018] Preferably, the organic solvent I and the organic solvent II are independently selected from methanol, ethanol, isopropanol, n-butanol, tetrahydrofuran (THF), acetone, and butanone.

[0019] In a third aspect, the present invention also provides the application of the multifunctional micro / nano fiber material for high-efficiency air filtration in the field of air filtration.

[0020] The multifunctional micro- / nanofiber material for high-efficiency air filtration described in this paper integrates metal-coordinated supramolecular self-assembly with an industrial meltblown process to innovatively design a hierarchical dual-scale fiber network, embedding ultrafine metal-organic supramolecular nanofibers within a biodegradable polylactic acid microfiber scaffold (MON@PM filter material). This filter material achieves high filtration efficiency and low air resistance while possessing excellent antibacterial properties, air permeability, and moisture management capabilities, providing a high-performance, scalable solution to addressing air pollution and public health challenges.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] (1) Improved filtration performance

[0023] a. Efficient particle capture capability:

[0024] The present invention uses nano-scale MON fibers (30-152nm) to construct an ultra-fine filtration network, which makes the PM2.5 particle filtration efficiency greater than 99.5%, and the filtration efficiency of the traditional melt-blown PLA non-woven fabric without stationary grade (78.2%) is increased by more than 11.3%.

[0025] Compared with traditional electret meltblown materials (which are easily affected by humidity), the material of the present invention can still maintain a filtration efficiency of >99% under a relative humidity of 80%, and its stability is improved by more than 30%.

[0026] b. Low air resistance and improved breathability:

[0027] The present invention optimizes the airflow channel through a dual-scale layered structure, while ensuring high filtration efficiency, reducing air resistance to 39Pa, which is 30%-50% lower than traditional high-efficiency electret filter materials (80-100Pa), and significantly improving breathing comfort.

[0028] (2) Enhanced humidity stability

[0029] Traditional electret meltblown non-woven fabrics will have reduced filtration efficiency due to electrostatic attenuation under high humidity conditions. However, the present invention uses metal-organic supramolecular self-assembled nanofibers and utilizes physical adsorption to enhance particle capture capabilities. It is not affected by external environmental factors and its humidity stability is increased by more than 2 times.

[0030] (3) Enhanced moisture permeability ensures breathing comfort

[0031] The enhanced capillary effect of the secondary nano-mesh and the hydrophilicity of silver ions make the MON@PM filter material prepared by the present invention have a density of 1472g / m 2 The water molecule permeability of 100g / m2 is significantly higher than that of PLA meltblown nonwoven fabric (419g / m2). 2 ·day.

[0032] (4) Antibacterial function, enhancing health protection

[0033] The material of the present invention contains Ag + , providing >99% antibacterial efficiency (against Escherichia coli, Staphylococcus aureus, etc.) through cell membrane destruction mechanism. Compared with traditional HEPA filter materials (without antibacterial function), it can effectively inhibit the growth of microorganisms and improve long-term safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 Raman spectra of xerogels obtained with different molar ratios of organic ligand L and metal salt (a is the Raman spectrum of organic ligand L; b is the molar ratio of organic ligand L to metal salt of 1:1, mass concentration of 0.224 wt%; c is the molar ratio of organic ligand L to metal salt of 2:3, mass concentration of 0.224 wt%; d is the molar ratio of organic ligand L to metal salt of 2:3, mass concentration of 1 wt%);

[0035] Figure 2 This is a scanning electron microscope image of filter-6 described in Example 1;

[0036] Figure 3 This is a scanning electron microscope image of the filter-8 described in Example 2;

[0037] Figure 4 This is a scanning electron microscope image of filter-10 described in Example 3;

[0038] Figure 5 This is a scanning electron microscope image of filter-12 described in Example 4;

[0039] Figure 6 This is a scanning electron microscope image of the MON@PM filter material described in Comparative Example 1;

[0040] Figure 7 This is a scanning electron microscope image of the MON@PM filter material described in Comparative Example 2;

[0041] Figure 8The filtration efficiency test results of the filter materials prepared in Examples 1 to 4 and Comparative Example 3 are shown in FIG. a, which is a comparison of filtration efficiency and pressure drop at a wind speed of 32 L / min, b is the DEHS particulate matter filtration efficiency, c is the quality factor, d is a comparison of filtration efficiency at different wind speeds, and e is a comparison of pressure drop at different wind speeds.

[0042] Figure 9 The water vapor permeability test results of the filter materials prepared in Example 3 and Comparative Example 3 are shown;

[0043] Figure 10 The air permeability test results of the filter materials prepared in Example 3 and Comparative Example 3 are shown;

[0044] Figure 11 The antibacterial test results of the filter materials prepared in Example 3 and Comparative Example 3 (a is the antibacterial image of Escherichia coli, b is the antibacterial image of Staphylococcus aureus, and c is the comparison of antibacterial rates);

[0045] Figure 12 The silver ion binding test results of the filter material prepared in Comparative Example 4 (a is a scanning electron microscope image, and b is an energy spectrum scanning image);

[0046] Figure 13 The silver ion binding test results of filter-6 prepared in Example 1 (a is a scanning electron microscope image, b is an Ag element spectrum image, and c is an organic ligand L / Ag + High-density transmission dark field image of a single supramolecular nanofiber, where d is the organic ligand L / Ag + Ag element energy spectrum of supramolecular nanofibers, Figure e is the XPS full spectrum scan, and Figure f is the XPS fine spectrum). DETAILED DESCRIPTION

[0047] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be understood as limiting the present invention.

[0048] Unless defined otherwise herein, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.

[0049] Where values are described herein as ranges, it should be understood that such disclosure includes disclosure of all possible sub-ranges within that range, as well as specific values falling within that range, regardless of whether a specific value or sub-range is explicitly stated.

[0050] In this document, "a plurality of" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or more than or equal to two.

[0051] In this document, the terms “preferably” and “more preferably” are only used to describe implementation methods or examples with better effects. It should be understood that they do not limit the scope of protection of the present invention.

[0052] In this document, the word "further" or the like is used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present invention.

[0053] In this article, the term "and / or" is used to describe an association relationship between objects, indicating that three relationships can exist. For example, A and / or B means: A or B, or A and B.

[0054] As used herein, the term "about" means + / - 10%, preferably + / - 5%, more preferably + / - 1% of the specified value.

[0055] In this document, the terms “include,” “including,” “have,” “contain,” etc. are open-ended terms, meaning including but not limited to.

[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention pertains. Although preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein can also be used in the practice or testing of the present invention.

[0057] In order to determine the optimal molar ratio of organic ligand L to metal salt, organic ligand L at different molar ratios was dissolved in THF to form solution A and metal salt was dissolved in THF to form solution B, which was mixed to obtain wet gel. After drying, dry gel was obtained. Raman spectroscopy analysis of organic ligand L, different molar ratios of organic ligand L to metal salt, and different concentrations of dry gel was performed. The results are shown in Figure 2. Figure 1 It is worth mentioning that for the same gel, there is no obvious difference in the pyridine peak between the wet gel and the dry gel except for the solvent peak, so only the results of the dry gel are shown. It can be clearly seen from the figure that when the molar ratio of organic ligand L to metal salt is 1, with the addition of AgNO3, the peak at 1000 cm -1 The breathing vibration peak of the pyridine ring ( Figure 1 b) Compared with the pure organic ligand L( Figure 1 a) is significantly reduced and almost disappears when the molar ratio of organic ligand L to metal salt is 2 / 3 ( Figure 1 c). Theoretically, 1000cm -1 The pyridine ring breathing vibration peak at + The coordination effect should shift to higher wavenumbers, but here it is similar to 1040cm -1The triangular mode peaks of the pyridine ring at the position overlap. + The coordination chemical properties of Ag are known to form a coordination with pyridine. The two pyridine groups are often connected to Ag in a right angle or a similar right angle manner. + Therefore, when the ligand L and Ag containing three pyridyl groups on both sides + When the reaction occurs, if the molar ratio of organic ligand L to metal salt = 2 / 3, it can ensure that pyridine can react with Ag. + The problem is that due to the poor solubility of L / Ag+ coordination polymer and the fast gelation speed, it is difficult to ensure that all pyridine groups on the organic ligand L can react with Ag when forming the gel. + Therefore, there will always be Ag that is not coordinated or only has one position coordinated. + Exists. Figure 1 Middle b, Figure 1 The two gels in Figure C are prepared at very low concentrations. If the concentration increases, the gelation speed will inevitably become faster, which means that the Ag cannot be fully coordinated. + There will be more, that is, more free pyridine groups. Figure 1 It is verified in d that the molar ratio of organic ligand L to metal salt is 2 / 3. As the concentration increases, the peak representing the free pyridine group is relatively Figure 1 The middle c becomes larger again.

[0058] The present invention will be described in detail below with reference to the embodiments.

[0059] Example 1: Preparation of MON@PM filter material

[0060] The MON@PM filter material of this embodiment includes a micron-sized fiber scaffold layer and a nanofiber layer grown on the micron-sized fiber scaffold layer. The nanofiber layer is synthesized from metal salt and organic ligand L by a self-assembly method.

[0061] 1.1 Materials and Equipment

[0062] Raw material: polylactic acid (PLA) (Mw=150,000);

[0063] Metal salt: AgNO3;

[0064] Organic ligand L: tris(3-pyridyl)benzene-1,3,5-tricarboxylate, structural formula:

[0065]

[0066] Organic solvent: methanol;

[0067] Equipment: meltblown spinning machine (sry-600).

[0068] 1.2 Preparation steps

[0069] 1. Preparation of PLA melt-blown scaffolds: PLA melt-blown scaffolds are prepared using a melt-blown spinning machine with a 1.5-meter-wide spinning die. During the preparation process, the polylactic acid melt is extruded through a screw extruder and a metering pump, and then decays into ultrafine fibers in high-speed hot air. Subsequently, the fibers are collected on a stainless steel sieve under negative pressure. The die and screw temperatures are set to 230°C and 220°C, respectively. The throughput of the polylactic acid (PLA) melt is approximately 0.1 g / min / hole, which is equivalent to a metering pump speed of 15 rpm. The hot air pressure at the die outlet is maintained at 0.04 MPa. Finally, a roller collection system is used to continuously collect the PLA melt-blown nonwoven, which is the PLA melt-blown scaffold;

[0070] 2. Preparation of MON nanofiber solution: Organic ligand L was dissolved in methanol to form solution A, with a mass fraction of solution A of 0.08%. 1.5 molar equivalents of AgNO3 relative to organic ligand L were dissolved in a water-methanol mixture (volume ratio of 4:5) to prepare solution B, with a mass fraction of solution B of 0.05%.

[0071] 3. Synthesis of MON@PM filter material: Using a dip-coating process, a PLA melt-blown scaffold was sequentially immersed in solution A and solution B, ensuring complete infiltration until the PLA melt-blown scaffold weight no longer increased. The treated PLA melt-blown scaffold was first air-dried at room temperature to facilitate the growth of supramolecular nanofibers, and then oven-dried to ensure complete removal of the solvent. The resulting MON@PM filter material, named filter-6, has a scanning electron micrograph (SEM) as shown below. Figure 2 shown.

[0072] Example 2

[0073] The only difference between the MON@PM filter material of this embodiment and that of Example 1 is that the mass fraction of solution A is 0.1%; the mass fraction of solution B is 0.06%. The rest is the same as that of Example 1. The prepared MON@PM filter material is named filter-8. The scanning electron microscope image thereof is shown in FIG. Figure 3 shown.

[0074] Example 3

[0075] The MON@PM filter material of this embodiment differs from that of Example 1 only in that the mass fraction of solution A is 0.13% and the mass fraction of solution B is 0.075%. The rest of the contents are the same as those of Example 1. The prepared MON@PM filter material is named filter-10. The scanning electron microscope image thereof is shown in FIG. Figure 4 shown.

[0076] Example 4

[0077] The only difference between the MON@PM filter material of this embodiment and that of Example 1 is that the mass fraction of solution A is 0.15% and the mass fraction of solution B is 0.09%. The rest is the same as that of Example 1. The prepared MON@PM filter material is named filter-12. The scanning electron microscope image thereof is shown in FIG. Figure 5 shown.

[0078] Example 5

[0079] The MON@PM filter material of this embodiment differs from that of Example 1 only in that the metal salt is FeNO 3 ; the rest are the same as those of Example 1.

[0080] Example 6

[0081] The MON@PM filter material of this embodiment differs from that of Example 1 only in that the metal salt is CuSO 4 ; the rest are the same as those of Example 1.

[0082] Example 7

[0083] The MON@PM filter material of this embodiment differs from that of Example 1 only in that the metal salt is ZnCl 2 ; the rest are the same as those of Example 1.

[0084] Example 8

[0085] The MON@PM filter material of this embodiment differs from that of Example 1 only in that the metal salt is CoCl 2 ; the rest is consistent with Example 1.

[0086] Example 9

[0087] The MON@PM filter material of this embodiment differs from that of Example 1 only in that the metal salt is Ni(NO 3 ) 2 ·6H 2 O; the rest are the same as those of Example 1.

[0088] Comparative Example 1

[0089] The only difference between the MON@PM filter material of this comparative example and that of Example 1 is that the mass fraction of solution A is 0.05%; the mass fraction of solution B is 0.03%; the rest are the same as those of Example 1. Figure 6 shown.

[0090] Comparative Example 2

[0091] The only difference between the MON@PM filter material of this comparative example and that of Example 1 is that the mass fraction of solution A is 0.18%; the mass fraction of solution B is 0.1%; the rest are the same as those of Example 1. Figure 7 shown.

[0092] Comparative Example 3

[0093] The filter material of this comparative example is the PLA melt-blown stent prepared in step 1 of Example 1, i.e., polylactic acid melt-blown cloth.

[0094] Comparative Example 4

[0095] The filter material of this embodiment is the PLA melt-blown bracket prepared in step 1 of Example 1, which is directly immersed in solution B, that is, polylactic acid melt-blown cloth-Ag.

[0096] The performance results of Examples 1 to 4 and Comparative Examples 1 to 2 are shown in Table 1:

[0097] Table 1 Tensile strength test results

[0098] Serial number Tensile strength (MPa) Example 1 5.7 Example 2 8.1 Example 3 10.5 Example 4 13.4 Comparative Example 1 No complete secondary nanonetwork is formed Comparative Example 2 The aperture of the secondary mesh is too small to be used for air filtration

[0099] Test Case

[0100] 1. Filtration efficiency test

[0101] Equipment: TOPAS AFC 131 filter tester;

[0102] Test conditions:

[0103] Particulate matter: DEHS aerosol (particle size 0.196-4.595μm);

[0104] Air flow rate: 1.9cm / s-14.2cm / s;

[0105] Relative humidity: 30%-80%;

[0106] Filtration area: 176.63cm 2 .

[0107] The results are as follows Figure 9As shown, compared to the polylactic acid meltblown fabric of Comparative Example 3, the addition of the nanofiber layer significantly improved filtration performance. All MON@PM filter materials exhibited filtration efficiencies exceeding 90%, with Filter-12 prepared in Example 4 achieving a filtration efficiency of 99.74%. For particles larger than 2.5 μm, all MON@PM filter materials demonstrated filtration efficiencies exceeding 99.99%. Airflow velocity generally affects filtration performance. MON@PM filter materials exhibited a significant drop in filtration efficiency at airflow velocities exceeding 8 cm / s. In contrast, Filter-10 prepared in Example 3 and Filter-12 prepared in Example 4 maintained high filtration efficiencies even at high airflow speeds of 14.2 cm / s, demonstrating the contribution of the stable secondary nanomesh structure to efficient particle interception. Furthermore, humidity had no significant effect on adsorption, with the MON@PM filter materials maintaining high filtration efficiencies exceeding 90% across a humidity range of 30% to 80%. After 120 hours of filtration testing, the filtration efficiencies for PM2.5 and PM10 remained unchanged. The results were remarkably stable at 99.88% and 99.91%, respectively. These findings demonstrate the excellent filtration durability and long-term performance of the engineered MON@PM filter material.

[0108] 2. Moisture permeability test:

[0109] Equipment: Moisture permeable cup;

[0110] Test method: GB / T 12704.1-2009;

[0111] The test results are as follows Figure 10 As shown, it can be seen that the water vapor transmission rate (WVTR) of the MON@PM filter material of the present invention reaches 1472 g / (m2·day), and the water vapor transmission rate of the polylactic acid meltblown nonwoven fabric of Comparative Example 3 is 419 g / (m2·day).

[0112] 3. Air permeability test:

[0113] Equipment: Fabric air permeability tester;

[0114] Test method: GB / T 24218.15-2018;

[0115] The results are as follows Figure 11 As shown, it can be seen that the air permeability of the MON@PM filter material of the present invention is 105.7 mm.s -1 The load of the secondary nanomesh did not change the air permeability too much. The air permeability of the polylactic acid meltblown nonwoven fabric of Example 3 was 99.1 mm.s -1 .

[0116] 4. Antibacterial test:

[0117] Test method:

[0118] Use a graduated cylinder to measure 100 mL of distilled water into a 250 mL reagent bottle. Using an analytical balance, weigh 2.5 g of LB broth and add the mixture. Sterilize in an autoclave at 121°C for 15 minutes before use. Use a graduated cylinder to measure 100 mL of distilled water into a 250 mL reagent bottle. Using an analytical balance, weigh 2.5 g of LB broth and 1.5 g of agar powder. Add the mixture and mix thoroughly. Sterilize in an autoclave at 121°C for 15 minutes. Once the culture has cooled to approximately 40-50°C, use an electric pipette to transfer 15 mL of the culture into a disposable sterile dish. Add 3 mL of LB liquid medium to a 12 mL bacterial culture tube. Pick a single colony from the E. coli and Staphylococcus aureus solid cultures and add it to the liquid culture. Incubate in a constant temperature shaker (37°C, 200 rpm) for 15 hours. The sample was cut into 4 equal parts (each weighing 12 mg), and one part of each was placed in a disposable sterile dish. Both sides were sterilized by ultraviolet irradiation for 30 minutes and set aside.

[0119] The experiment was divided into control group and experimental group. The experimental group was divided into group 1 and group 2, and each group was repeated once. Escherichia coli and Staphylococcus aureus were diluted to 10 6 CFU / mL, then add the corresponding samples according to grouping, and add 25 μL of the diluted bacterial suspension. The co-culture solution is placed in a 37°C constant temperature incubator and incubated for 18 hours. After incubation, rinse with 5 mL of sterile PBS, then make a serial 10-fold dilution with sterile PBS. 100 μL of each dilution is evenly spread on LB solid medium. Incubate in a 37°C constant temperature incubator for 18 hours, remove, photograph, and record the number of colonies.

[0120] The results are as follows Figure 11 As shown, it can be seen that the antibacterial rates of the MON@PM filter material of the present invention against Escherichia coli and Staphylococcus aureus are both greater than 99.9%.

[0121] 5. Silver ion release test

[0122] Equipment: Inductively coupled plasma mass spectrometer (ICP-MS, 7800(MS), Agilent, USA);

[0123] Test method: The MON@PM filter material prepared in Example 1 was cut into 2.50 cm × 2.50 cm squares and placed in 100.00 mL of deionized water at room temperature. 10.00 mL of sample solution was removed at predetermined intervals for ICP-MS analysis.

[0124] The results showed that the total amount of silver ions released by the MON@PM filter material within seven days was 0.78 μg / mL, which was higher than the minimum concentration required for effective antibacterial activity in aqueous systems (0.01 μg / mL), but lower than the half-lethal concentration (LD50) of cells in vitro. 50 =1.42 μg / mL).

[0125] 6. Silver ion binding test

[0126] The MON@PM filter material prepared in Example 1 and the polylactic acid meltblown cloth-Ag prepared in Comparative Example 4 were subjected to high-magnification transmission electron microscopy scanning and energy spectrum scanning analysis, respectively. The results are as follows: Figure 12 and Figure 13 As shown in the scanning electron microscope (SEM) and energy spectrum scanning (EDS), the polylactic acid meltblown cloth-Ag ( Figure 12 a and Figure 12 In b), the silver ions are distributed over the entire surface of the meltblown fabric and are not attached to the fibers individually.

[0127] Comparison of the MON@PLA filter material of the present invention ( Figure 13 c. Figure 13 The scanning electron micrograph and energy spectrum in (d) show that silver ions are more tightly bound to the surface of the MON@PM filter material. Silver ions form a stronger bond with the nanofiber surface through supramolecular self-assembly, resulting in a more uniform and dense distribution of silver across the fibers.

[0128] Figure 13 The transmission electron microscopy (TEM) image in c shows that agglomerated silver nanoparticles are evenly distributed on the MON@PM filter material. These silver nanoparticles are clearly nanosized and distributed on the fiber surface, indicating the aggregation of silver in the form of nanoparticles. In addition, the XPS full spectrum and fine spectrum ( Figure 13 e and Figure 13 f) Further evidence of the presence of silver nanoparticles. XPS analysis confirmed that silver ions formed a relatively stable silver nanoparticle structure on the surface of the supramolecular nanofibers. Due to their small size and uniform distribution, silver nanoparticles generally have low toxicity. The low toxicity of silver nanoparticles, especially when they are small and evenly dispersed, can reduce their potential risks to the environment and organisms.

[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A multifunctional micro / nano fiber material for high-efficiency air filtration, characterized by: The multifunctional micro / nano fiber material comprises a micron-sized fiber scaffold layer and a nanofiber layer grown on the micron-sized fiber scaffold layer. The nanofiber layer is synthesized from a metal ion donor and an organic ligand L by a self-assembly method. The organic ligand L is tris(3-pyridyl)benzene-1,3,5-tricarboxylate, and its structural formula is:

2. The multifunctional micro / nano fiber material for high efficiency air filtration according to claim 1, characterized in that: The metal ion donor is a metal salt, and the metal salt is a silver metal salt, a copper metal salt, a cobalt metal salt, a zinc metal salt, a nickel metal salt or a trivalent iron metal salt.

3. The multifunctional micro / nano fiber material for high efficiency air filtration according to claim 1, characterized in that: The silver metal salt is selected from one or more of AgNO3, AgBF4, AgClO4, and AgCF3SO3, the trivalent iron metal salt is FeNO3, the copper metal salt is CuSO4, the zinc metal salt is ZnCl2, the cobalt metal salt is CoCl2, and the nickel metal salt is Ni(NO3)2·6H2O or NiCl2·6H2O.

4. The multifunctional micro / nano fiber material for high efficiency air filtration according to claim 2, characterized in that: The metal salt is a silver metal salt or a trivalent iron metal salt.

5. The multifunctional micro / nano fiber material for high efficiency air filtration according to claim 1, characterized in that: The molar ratio of the organic ligand L to the metal salt is 2:

3.

6. The multifunctional micro / nano fiber material for high efficiency air filtration according to claim 1, characterized in that: The micron-scale fiber scaffold layer is made of polylactic acid with a weight-average relative molecular mass Mw of 100,000-300,000 and is prepared by a melt-blowing process.

7. A method for preparing the multifunctional micro / nano fiber material for high efficiency air filtration according to any one of claims 1 to 6, characterized in that: The steps include: S1: melt-blown process to prepare the polylactic acid scaffold layer; S2: dissolving an organic ligand L in an organic solvent I to form a solution A, and dissolving a metal salt in an organic solvent II to form a solution B, wherein the molar ratio of the organic ligand L to the metal salt is 2:3; S3: The polylactic acid scaffold layer prepared in step S1 is sequentially immersed in solution A and solution B for dip coating. The polylactic acid scaffold layer after dip coating is air-dried and dried at room temperature to obtain a multifunctional micro / nano fiber material.

8. The method for preparing a multifunctional micro / nano fiber material for high efficiency air filtration according to claim 7, characterized in that: The mass fraction of the ligand L in the solution A is 0.08%-0.15%; and / or The mass fraction of the metal salt in the solution B is 0.05%-0.09%.

9. The method for preparing a multifunctional micro / nano fiber material for high efficiency air filtration according to claim 7, characterized in that: The organic solvent I and the organic solvent II are independently selected from methanol, ethanol, isopropanol, n-butanol, tetrahydrofuran, acetone, and butanone.

10. Use of the multifunctional micro / nano fiber material for high-efficiency air filtration according to any one of claims 1 to 6 in the field of air filtration.

Citation Information

Patent Citations

  • Preparation method for rapidly growing metal organic framework derivative with assistance of metal salt

    CN113054207A

  • Nanofiber filtering protective material with photocatalytic detoxification function and preparation method thereof

    CN113117418A

  • Nanofiber filter material

    CN216223329U

  • Apparatus for operating HVDC

    KR1020230070438A

  • Window regulator assembly of a vehicle

    KR1020230151910A